Evolutionary bioinformatics - Forsdyke, Donald R.; SpringerLink (Online service). (New York, NY Springer New York, 2011)
Books on bioinformatics which began appearing in the mid 80s primarily served gene-hunters, and biologists who wished to construct family trees showing tidy lines of descent. Given the great pharmaceutical industry interest in genes, this trend has continued in most subsequent texts. These deal extensively with the exciting topic of gene discovery and searching databases, but hardly consider genomes as information channels through which multiple forms and levels of information, including genetic information, have passed through the generations
Electronic reproduction.
Keywords: Bioinformatics; Evolutionary genetics; Genomes; Electronic books